PARTICIPATORY INSTITUTIONAL ASSESSMENT IN EARLY CHILDHOOD EDUCATION PATHS, CHALLENGES AND POTENTIALS IN a PAULISTAN DAYCARE - Silva, Tassio Jose da [UNESP] (Centro Univ Nove Julho, 2022)
The debate on the quality of early childhood education has gained prominence on the national and international scene from different political projects that paradoxically dispute quite different conceptions of early childhood education, society and children themselves. Thus, through the analysis of Sao Paulo experience expressed in the document Quality Indicators of Early Childhood Education in Sao Paulo, in force since 2013, this article problematizes how Participatory Institutional Assessment (PIA) has been applied in educational centers and which process, challenges and potentials permeate the development of this type of assessment in Early Childhood Education. The theoretical perspectives that lead these reflections come from public policies for evaluation and quality of Early Childhood Education. In a qualitative approach, we present an ethnography carried out in 2018 in a Child Education Center in the city of Sao Paulo, assuming as a basic assumption the fact that the implementation of public policies inevitably configures itself as a dynamic permeated by tensions and negotiations. However, the reflective path followed in this thesis allows us to affirm the fundamental role of the development of PIA in the quality of early childhood education, since it promotes the systematic and continuous movement of discussion of the pedagogical political project, in dialogue with the guidelines that guide child education in Brazil.
Keywords: child education; participation; participatory institutional assessment; quality; self-assessment